The Impact of Using Educational and Digital Games on Middle School Students Science Achievement - Ivgin, Asli Bahar; Akcay, Hakan (INT SOC TECHNOLOGY EDUCATION & SCIENCE-ISTES, 2024)
Game-based learning has attracted great interest in science education as an effective way to increase student achievement. Most studies in this field have focused on digital or non-digital games. In the literature, some studies generally compare educational games with traditional teaching methods. More studies need to be conducted to compare the effects of digital and non- digital games on achievement. For this reason, the study's primary purpose is to examine the impact of different types of games, namely educational and digital games, and their combinations on students' academic achievement and views on the learning process. In this context, the researcher used three different methods to be applied to three experimental groups and one control group. The research was carried out on 77 5th-grade students studying in a public school in Turkey. Both quantitative and qualitative research methods were used in the quasi-experimental design. Data were obtained through the 'Human and Environment Unit Achievement Test' and semi-structured interviews. The results showed that students in the educational and digital games sections were significantly better at science achievement than students in the textbook-oriented section. No significant difference was found between the digital game-based and educational game-based students in terms of achievement. The academic achievement of the group in which these two game types were used together was higher than the others. In addition, most students were satisfied with the using educational and digital games in science lessons and found the games fun and motivating.
Keywords: Educational games; Digital games; Science education; Academic achievement; ARGUMENTATIVE DISCOURSE; TEACHER PERCEPTIONS; EPISTEMIC BELIEFS; ENGAGING STUDENTS; ENGAGEMENT; GAMIFICATION; MOTIVATION; SKILLS; PLAY; METAANALYSIS; Education & Educational Research